A new phenomenon of cochlear otosclerosis: an acquired or congenital disease? – A clinical report of cochlear otosclerosis. (1st June 2021) - Lu, Simeng; Wei, Xingmei; Chen, Biao; Chen, Jingyuan; Zhang, Lifang; Yang, Mengge; Sun, Zhiming; Shi, Ying; Kong, Ying; Liu, Sha; Li, Yongxin
Abstract: Background: No cochlear otosclerosis in infants with congenital bilateral SNHL has been reported. Aims/Objectives: We report an infant male with bilateral cochlear otosclerosis, suggesting that cochlear otosclerosis may be a congenital disease and to further analyze the etiology of and genetic expression in congenital bilateral cochlear otosclerosis. We also describe the clinical characteristics and experience of patients with bilateral cochlear otosclerosis treated with cochlear implants (CIs). Materials and Methods: Seven patients, including an infant, who were diagnosed with cochlear otosclerosis underwent CI surgery. Their medical records, audiological and radiological results, surgical procedures, and CI outcomes were collected and reviewed. Results: The median age at hearing loss was 38 years, ranging from 0 to 47 years. The child had bilateral hearing loss at birth and received a CI at 1 year of age. He also had growth retardation and was diagnosed with 3q+/3p- syndrome. All patients (8 ears) had better postoperative auditory performance than that preoperatively. Conclusions and Significance: Although cochlear otosclerosis often starts at middle age and progresses slowly, it may be a congenital disease that is related to chromosome abnormality. This disease presents with SNHL or MHL, and treatment with a CI is beneficial.